Infertility in Men with Spinal Cord Injury: Research and Treatment - Nancy L. Brackett (Scientifica)
Spinal cord injury (SCI) occurs most often to young men. Following SCI, most men are infertile due to a combination of erectile dysfunction, ejaculatory dysfunction and semen abnormalities. Erectile dysfunction may be treated by the same therapies that are used in the general population. Similarly, the same treatments that are effective to assist conception in couples with non-SCI male factor patients are effective in assisting conception in SCI male-factor patients. The most apparent differences in male-factor symptoms between SCI and non-SCI patients are the high occurrences of anejaculation and atypical semen profiles in men with SCI. Methods available to assist ejaculation in men with SCI include penile vibratory stimulation and EEJ. Use of surgical sperm retrieval as the first line of treatment for anejaculation in men with SCI is controversial. Most men with SCI have a unique semen profile characterized by normal sperm concentration, but abnormally low sperm motility. Toxic substances in the semen contribute to this problem. Despite impaired sperm parameters, pregnancy outcomes using sperm from men with SCI are similar to pregnancy outcomes using sperm from non-SCI men. Future studies should focus on improving natural ejaculation and improving semen quality in these men.